MitImpact 3: modeling the residue interaction network of the Respiratory Chain subunits. Issue Volume 49:Issue D1(2021) (9th December 2020) - Castellana, Stefano; Biagini, Tommaso; Petrizzelli, Francesco; Parca, Luca; Panzironi, Noemi; Caputo, Viviana; Vescovi, Angelo Luigi; Carella, Massimo; Mazza, Tommaso
Abstract: Numerous lines of evidence have shown that the interaction between the nuclear and mitochondrial genomes ensures the efficient functioning of the OXPHOS complexes, with substantial implications in bioenergetics, adaptation, and disease. Their interaction is a fascinating and complex trait of the eukaryotic cell that MitImpact explores with its third major release. MitImpact expands its collection of genomic, clinical, and functional annotations of all non-synonymous substitutions of the human mitochondrial genome with new information on putative Compensated Pathogenic Deviations and co-varying amino acid sites of the Respiratory Chain subunits. It further provides evidence of energetic and structural residue compensation by techniques of molecular dynamics simulation. MitImpact is freely accessible at http://mitimpact.css-mendel.it .